IPR-Based Sustainable Tourism: Comparative Analysis of Indonesia, Malaysia, and Thailand - Disemadi, Hari Sutra; Bajury, Mimi Sintia Mohd; Nurlaily, Nurlaily; Anggraini, Ratih; Sihombing, Dame Afrina (Legality : Jurnal Ilmiah Hukum, 2026)
This article discusses the potential of IPR-based sustainable tourism in Indonesia, Malaysia, and Thailand, three Southeast Asian countries with immense cultural resources that can further develop the tourism industry. This analysis primarily assesses the adequacy of the relevant regulatory frameworks in bridging sustainability and tourism, particularly by utilising the relevant IPR regimes. Employing the normative legal research method, this study finds that all three countries are for the most part, normatively inadequate to adopt an IPR-based sustainable tourism system, due to the lack of emphasis on ‘social interests’ with regards to community development and its connection with the bigger and more urgent objective of environmental sustainability. However, the study also notes that Indonesia stands out as the country with the most comprehensive and locally sensitive IPR frameworks. These frameworks potentially facilitate a harmonious connection between the three domains through the perspective of Roscoe Pound’s Sociological Jurisprudence, specifically how law is viewed as an instrument for social engineering, which serves the objective of moving the tourism sector and its stakeholders towards a more sustainable approach.